Improving money's worth ratio calculations: The case of Singapore's pension annuities - FONG, Joelle H. Y. (Institutional Knowledge at Singapore Management University, 2014)
This article contributes to a better understanding of the risks involved in a life annuity investment. We examine the distribution of weighted annuity benefits and assess various measures of dispersion such as the coefficient of variance. In particular, we quantify the standard deviation about the expected value, thereby extending the usefulness of the popular money’s worth framework for annuity valuation. The effort toward a more detailed and more accurate risk picture of investing in annuities enables retirees to differentiate among products that may appear seemingly uniform in terms of money’s worth, but vary widely in terms of their risk attributes.